A randomized trial of automated intermittent ropivacaine administration vs. continuous infusion in an interscalene catheter. Issue 1 (16th October 2017) - Oxlund, J.; Clausen, A. H.; Venø, S.; Nielsen, M. D.; Pall, M.; Strøm, T.; Toft, P.
Abstract : Background: Ultrasound‐guided interscalene nerve block with ropivacaine as local anesthetic agent given as boluses or continuous infusion is the preferred pain management after major shoulder surgery. The use of automated intermittent boluses has been shown to be superior to continuous infusion in sciatic and epidural nerve block. Hypothesis: Automated intermittent boluses reduce pain after major shoulder surgery. Methods: Seventy patients aged 18–75 years, scheduled for major shoulder surgery under general anesthesia with interscalene nerve block were included in this randomized controlled trial. Patients were allocated to either automated intermittent boluses with 16 mg ropivacaine every 2 h combined with patient‐controlled administration or to a conventional regimen of continuous infusion of 8 mg/h (4 ml/h) of ropivacaine combined with patient controlled administration (2 ml, lockout time 30 min). Pain (Visual Analog Scale, VAS) was assessed every 8 h postoperatively. Results: Fifty‐seven patients completed the study, 29 in the continuous infusion group and 28 in the automated intermittent bolus group. Shoulder arthroplasty was performed in 49 (86%) of the cases. There were no significant differences in VAS score from 8 to 48 h post‐operatively. No significant difference in opioid usage was observed. The automated intermittent bolus group reported significantly less force on coughing and more hoarseness. A significantly lower volume of ropivacaine was used in the automated intermittent bolus group. Conclusion: Automated intermittent boluses did not reduce pain or rescue opioid consumption compared with continuous infusion of ropivacaine. The automated intermittent bolus group had significantly less force on coughing and more hoarseness.